Detection unlimited - Heyer, Georgette (Naperville, Ill. : Sourcebooks Landmark, 2010)
Chief Inspector Hemingway investigates the murder of village solicitor Sampson Warrenby, a man with an abundance of enemies.
Originally copyrighted in 1953.
Keywords: Hemingway, Inspector (Fictitious character); Police -- Great Britain; Mystery fiction